Review paperNew direction in diabetes treatment – incretinomimetics and DPP-4 inhibitors - Znaniecka, Michalina; Rutkowska, Joanna; Bandurska-Stankiewicz, Elżbieta (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2010)
Incretin hormones are produced and released from intestine during food digesting. There are two incretin hormones: glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic peptide (GIP). Both of them stimulate pancreatic  cells to release insulin. Only 20% of GLP-1 released from intestine reach  cells, mainly due to the dipeptidyl peptidase-4 enzyme (DPP-4) actions. DPP-4 inactivates GLP-1 in 4-5 min. In healthy persons incretin hormones are responsible for up to 70% of insulin release after a meal. In type 2 diabetes (DM2) incretin effect is disturbed. Exogenous administration of GLP-1 and GIP restore early phase of insulin release in DM2 patients. Late phase of insulin release is re-established only after GLP-1 administration. That is why only GLP-1 is used in therapy of DM2. There are two strategies of DM2 treatment, which involve intervention in incretin axis. First of them is administration of GLP-1 receptor agonist – exenatide or GLP-1 analog – liraglutide. Second of them is based on inhibition of DPP-4 enzyme – sitagliptin, vildagliptin or saksagliptin. All of those strategies regulate glucose level in blood, but only GLP-1 receptor agonist and GLP-1 analog may also cause body mass reduction. This work describes mechanism of action of incretin based drugs and also summarizes results of third phase of clinical studies.